Pola Bilangan pada Usia Sekolah SMP di Desa Persiapan Talim - Maktisen Ena; Landerius Maro (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
This service aims to improve learning outcomes and the process of learning mathematics in this case, number patterns that are more active, creative and enjoyable. The process of learning mathematics in school-age children greatly influences when they go to school later. Some students feel that learning number patterns is helped and some students feel very difficult, this service activity is supported by the Student Creativity program that passed the Ministry's grant funding. The process of learning number patterns greatly impacts when they learn mathematics in this case, number patterns, therefore we are present in delivering material about number patterns in the village of Talim Preparation, North Central Alor District, Alor Regency. This activity went well, the results obtained by many students began to develop in terms of learning number patterns. The activity was carried out in the village office room, the enthusiasm of junior high school students was very good. In the process of learning mathematics about number patterns by applying realistic, it can run well and can improve the quality and learning outcomes of junior high school students.